THE CONTENT AND THE PHYSICO-CHEMICAL CHARACTERISTICS OF ALGINATB EXTRACTED FROM THREE SPECIES OF BROWN ALGAE (S. cinereum; H. triquetra; and T. conoides) - Tharnrin Wikanta; D.S. Rejeki; L. Rahayu (Research Center for Fisheries, 1998)
Three species of brown algae (Sargassum cineruem, Hormophysa triquetra, and, Turbinaria conoides) harvested from Pari Island of the Seribu Islands, North Jakarta, in November 1992 were used for this study.